Deep Learning Implementation in Islamic Education: Integrating Pedagogical Approaches and Islamic Values - Dian Permana; Masruri; Ratri Diana; Multazom; Izzah Munisah Farhati (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The rapid development of artificial intelligence and digital technologies has significantly transformed educational practices, including Islamic education. This study aims to explore the implementation of deep learning in Islamic education by examining its pedagogical dimensions and its compatibility with Islamic values. Using a qualitative library research approach, this study analyzes relevant literature on deep learning technologies, educational pedagogy, and Islamic educational philosophy. The findings indicate that deep learning has considerable potential to enhance personalized learning experiences, adaptive assessment, intelligent tutoring systems, and data-driven instructional strategies in Islamic educational institutions. From a pedagogical perspective, deep learning supports student-centered learning, critical thinking, collaborative engagement, and higher-order cognitive skills that are essential in twenty-first-century education. Furthermore, the integration of Islamic values such as tauhid (monotheism), akhlaq (moral conduct), amanah (responsibility), and ihsan (excellence) provides an ethical framework for the implementation of artificial intelligence technologies in educational settings. The study concludes that the successful implementation of deep learning in Islamic education requires a balanced integration between technological innovation, pedagogical effectiveness, and Islamic ethical principles to ensure that digital transformation contributes to holistic human development. This research contributes to the growing discourse on interdisciplinary approaches linking educational technology, pedagogy, and Islamic studies in the era of digital transformation.